Performance Analysis of Islamic Rural Banks (BPRS) with The Maqasid Sharia Approach as An Investment Decision-making Tool - Wildan Mashfufah; Mukhamad Yasid (Tazkia Islamic Finance and Business Review, 2020)
This study aims to measure the performance of BPRS and their ranking using Maqasid-based Performance Evaluation Model (MPEM). This paper is also intended to understand whether the results of BPRS performance measurement based on maqasid will be used as an investment decision-making tool by investors. The data used in this study are questionnaire interviews with BPRS investors, and quarterly BPRS financial statements for the period 2017-2018 with a sample of 48 out of 168 BPRS in Indonesia. The methods used are Sekaran, The Simple Additive Weighting (SAW), and the questionnaire. The results show some findings. First, MPEM can be implemented in measuring the performance of BPRS, notwithstanding some ratios that are used in MPEM are not disclosed in the BPRS financial statements and not all ratios that are needed to measure the performance of BPRS exist in MPEM. Second, BPRS Berkah Ramadhan is excellent in the dimensions of religious preservation, Harta Insan Karimah Kota Tegal is in safeguarding life, and Way Kanan is in stakeholder protection. Third, investors make Islamic conformity as the main reason when investing in BPRS, accordingly performance measurement using the maqasid sharia approach is a must and the result will be used as a tool in investment decision-making.